Board Gender Diversity and CSR Reporting: Evidence from Jordan - Amer Al Fadli; John Sands; Greg Jones; Claire Beattie; Dom Pensiero (Australasian Accounting, Business and Finance Journal, 2019)
This study investigates whether board gender diversity influences corporate social responsibility (CSR) reporting in Jordan, where there are no gender board balance regulatory requirements. Data was examined from all non-financial Jordanian listed companies for the period of 2006 to 2015. This longitudinal data results in balanced panel data of 800 observations. A content analysis method was used to obtain the reporting index of CSR disclosure in the annual reports. Ordinary least square regression showed that the presence of female directors on a board has a significantly positive effect on the level of CSR reporting. The presence of female directors on the board appears to play a significant role in enhancing compliance with corporate governance best practices. These results provide motivations for companies to consider gender balance on boards. Further, these results reinforce the decision making of regulators in countries where policies have been adopted to increase female representation on corporate boards. In countries where no such regulation exists the inclusion of gender balance practices within boards of directors may increase the level of CSR reporting practices. This study can be considered as one of the few empirical studies that have evaluated the impact of board gender diversity on the level of CSR reporting in a context where there are no gender balance strategies or policies.
Keywords: Board gender diversity; CSR Reporting; Jordan; Middle East; Legitimacy Theory